LEGAL PROTECTION IN THE CRIMINAL ACTION OF PROTECTED WILD LIFE TRAFFICKING (Decision Study Number 1260 / Pid.B / LH / 2019 / PN Sby) - Wartisah Winaningsih (2020)
This research was conducted to identify and explain about the legal protection system of wildlife in criminal acts. In addition, to find out and explain about the optimization of legal measures against the obstacles faced in protecting wildlife so that wildlife trade does not occur. The theory used is the theory of will, theory of legal protection, theory of law enforcement, theory of punishment, and theory of criminal liability. The research method used is normative law research by reviewing statutory regulations. The subject of the study is the law conceptualized as norms or rules that apply in society and become a reference for everyone's behavior. The results of this study are formulated that in order to provide legal protection it is inseparable from the implementation of law enforcement against illegal wildlife trade which requires law enforcement institutions and law enforcement officials. In a narrow sense, law enforcement officers are people involved in the process of upholding the law starting from witnesses, police, legal advisors, prosecutors, judges, and prison guard officers. Supervision as a preventive measure for the illegal trade of protected animals is carried out at the activity level of taking or catching specimens of wild plants and animals, monitoring domestic circulation, and monitoring to and from abroad. The conclusion is that the protection system in criminal acts as stipulated in the prevailing laws and regulations in Indonesia against protected wild animals is not able to suppress the crime of wildlife trafficking because the punishment for the perpetrator does not cause a deterrent effect even the state is harmed by the actions of the illegal wildlife trade actors extinction of protected wildlife. Optimizing legal remedies in terms of laws and regulations regarding the criminal act of trafficking wild animals in their punishment is not able to provide a deterrent effect for the perpetrators of criminal acts, so a paradigm of restorative justice can be applied to values that can encourage the whole community to social conditions that contribute to the behavior of the offender where the crime The trade in wild animals is driven by economic factors that want greater profits by trading wild animals, so it is necessary to improve synergic coordination between government agencies in providing education for people living around protected wildlife habitats to prevent the re-occurrence of trade in protected wildlife by state.